Three-year results from the Retro-IDEAL study: Real-world data from diabetic macular edema (DME) patients treated with ILUVIEN® (0.19 mg fluocinolone acetonide implant). Issue 2 (March 2020) - Augustin, Albert J; Bopp, Silvia; Fechner, Martin; Holz, Frank; Sandner, Dirk; Winkgen, Andrea-M; Khoramnia, Ramin; Neuhann, Thomas; Warscher, Marcus; Spitzer, Martin; Sekundo, Walter; Seitz, Berthold; et al.
Introduction: The Retro-IDEAL (ILUVIEN Implant for chronic DiabEtic MAcuLar edema) study is a retrospective study designed to assess real-world outcomes achieved with the ILUVIEN® (0.19 mg fluocinolone acetonide (FAc)) in patients with chronic diabetic macular edema (DME) in clinical practices in Germany. Methods: This study was conducted across 16 sites in Germany and involved 81 eyes (63 patients) with persistent or recurrent DME and a prior suboptimal response to a first-line intravitreal therapy (primarily anti-VEGF intravitreal therapies). Results: Patients were followed-up for 30.8 ± 11.3 months (mean ± standard deviation) and had a mean age of 68.0 ± 10.4 years. Best-recorded visual acuity (BRVA) improved by +5.5 letters at month 9 (P ⩽ 0.005, n=56; from a baseline of 49 letters) and this was maintained through to month 30 (P ⩽ 0.05, n = 42). There was a concurrent improvement in central macular thickness with a reduction from 502 µm at baseline to 338 µm at year 1 (P ⩽ 0.0001, n = 43). This effect was sustained to year 3 (i.e. 318 µm; P ⩽ 0.0001, n = 29). Mean intraocular pressure (IOP) remained constant between baseline and year 3 with a peak change of 1.9 mm Hg occurring at year 1. Elevated IOP was observed in a similar percentage of patients prior to (22.2% of cases) and following (27.2%) treatment with the FAc implant. In the majority of cases, these elevations were managed effectively with IOP medications. Conclusions: Despite substantial amounts of prior intravitreal treatments – primarily with anti–vascular endothelial growth factor (VEGF) drugs – this real-world study showed that sustained structural and functional improvements can last for up to 3 years with a single FAc implant.